2006
DOI: 10.1002/adsc.200505465
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Cytochrome P450 BM3 for Terminal Alkane Hydroxylation

Abstract: Enzymes that catalyze the terminal hydroxylation of alkanes could be used to produce more valuable chemicals from hydrocarbons. Cytochrome P450 BM3 from Bacillus megaterium hydroxylates medium-chain fatty acids at subterminal positions at high rates. To engineer BM3 for terminal alkane hydroxylation, we performed saturation mutagenesis at selected active-site residues of a BM3 variant that hydroxylates alkanes. Recombination of beneficial mutations generated a library of BM3 mutants that hydroxylate linear alk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
78
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(85 citation statements)
references
References 60 publications
6
78
0
1
Order By: Relevance
“…Indeed, these enzymes can transform naphthalene into 1-naphthol by either harnessing the peroxide shunt pathway or through their natural NAD(P)H dependent activity. [12][13][14][15] More recently, directed evolution of toluene orthomonooxygenase (TOM) with a whole-cell biocatalytic system was described. [16][17][18] However, the poor enzyme stability and the reliance on expensive redox cofactors and reductase domains have precluded the practical application of these enzymes in specific industrial settings.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, these enzymes can transform naphthalene into 1-naphthol by either harnessing the peroxide shunt pathway or through their natural NAD(P)H dependent activity. [12][13][14][15] More recently, directed evolution of toluene orthomonooxygenase (TOM) with a whole-cell biocatalytic system was described. [16][17][18] However, the poor enzyme stability and the reliance on expensive redox cofactors and reductase domains have precluded the practical application of these enzymes in specific industrial settings.…”
Section: Introductionmentioning
confidence: 99%
“…Here again, molecules that are not fatty acids are typically not accepted as substrates because the carboxylate group is required for catalytic activity. Although many mutagenic studies have been performed with P450 BM3 with respect to broadening the substrate scope [34][35][36][37][38][39][40][41][42][43][44], this study demonstrated that perfluorocarboxylic acids (PFCs) can be used as decoy molecules to expand the substrate scope of P450 BM3 without resorting to mutagenesis. PFCs are a great alternative to fatty acids because many of the physical properties are maintained, while the greater bond energy of C-F (116 kcal mol −1 ) compared to that of C-H (95-99 kcal mol −1 ) renders them inert toward oxidation [30].…”
Section: Perfluorinated Fatty Acidsmentioning
confidence: 93%
“…[102,103] Arnold und Mitarbeiter haben beachtliche Anstrengungen unternommen, um mithilfe der molekularen gerichteten Evolution die Spezifität von P450 BM3 bezüglich Fettsäuren auch auf kurzkettige Alkane zu übertragen. [8,34,[104][105][106][107] Die am besten entwickelten Varianten enthalten Mutationen in beiden Subdomänen und zeigen eine hohe Aktivität für gasfçrmige Alkane und endlich auch für Ethan (Tabelle 1, Nr. 11 und 12).…”
Section: Die Gerichtete Evolution Von P450 Bm3unclassified